1971
DOI: 10.1002/art.1780140510
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro responses to autologous IgG in patients with rheumatoid arthritis

Abstract: The presence of rheumatoid factor in patients with rheumatoid arthritis remains unexplained and may be etiologically important. An attempt has been made to determine whether patients with seropositive rheumatoid arthritis show basic immunologic responses to IgG. Various immunologic parameters of antigen recognition were measured in 9 patients and 3 controls. No immediate or delayed cutaneous hypersensitivity was noted to native or aggregated autologous IgG, nor could in vitro lymphocyte blast cell transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Our results confirm the findings of other investigators (10,11) who demonstrated that lymphoid cells of blood from RA patients did not differ significantly from those of normal controls with respect to their in vitro responses to the various globulin preparations. Kinsella in a preliminary report (13) was able to demonstrate a higher response of RA blood lymphocytes to the aggregate HGG than that of normal blood lymphocytes.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm the findings of other investigators (10,11) who demonstrated that lymphoid cells of blood from RA patients did not differ significantly from those of normal controls with respect to their in vitro responses to the various globulin preparations. Kinsella in a preliminary report (13) was able to demonstrate a higher response of RA blood lymphocytes to the aggregate HGG than that of normal blood lymphocytes.…”
Section: Introductionsupporting
confidence: 92%
“…DISCUSSION Previous attempts to demonstrate in vitro transformation of lymphocytes from rheumatoid patients upon incubation with the various globulin preparations have been unsuccessful (10,11). We felt that further study of this question was needed for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Three reports have shown negative responses of RA lymphocytes to human IgG (6)(7)(8). Kinsella (9), on the other hand, has reported transformation of RA lymphocytes by IgGagg in the presence of fresh autologous plasma: and Dorner et a1 (10) demonstrated lymphocyte transformation by autologous IgG in the presence of RA serum.…”
Section: Enhancement Of In Vitro Immunoglobulin Synthesis Of Rheumatomentioning
confidence: 99%
“…Contrary to the foregoing, there has been no unequivocal demonstration that cell-mediated illmmuniity involv ing Fli is imiiplicated in the pathogenesis of rheumatoid inflammation. In particular, in vivo studies employilg delayed hypersensitivity skin responses to native-and( aggFII (10,11) and the intra-articular injection of purified FII into human volunteers (12), have not resolved this question. Because of controversial results derived from such in vivo studies (10)(11)(12)(13) others have relied oIn in vitro techniques, including in vitro lymphocyte transformation whiclh is known to be a reliable correlate of cell-mediated immuinity (14), to investigate possible roles for Fli and RF in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in vivo studies employilg delayed hypersensitivity skin responses to native-and( aggFII (10,11) and the intra-articular injection of purified FII into human volunteers (12), have not resolved this question. Because of controversial results derived from such in vivo studies (10)(11)(12)(13) others have relied oIn in vitro techniques, including in vitro lymphocyte transformation whiclh is known to be a reliable correlate of cell-mediated immuinity (14), to investigate possible roles for Fli and RF in the pathogenesis of RA. Unfortunately, recent studies have reported that neither isolated FII (11,15,16) nor isolated RF (17) can consistently induce in vitro transformation of peripheral blood lymphocytes of subjects with RA.…”
Section: Introductionmentioning
confidence: 99%